Electronic voting : 4th International Joint Conference, E-Vote-ID 2019, Bregenz, Austria, October 1-4, 2019, Proceedings /: 4th International Joint Conference, E-Vote-ID 2019, Bregenz, Austria, October 1-4, 2019, Proceedings. (2019) - Unknown
No abstract available